2021
DOI: 10.1111/cga.12435
|View full text |Cite
|
Sign up to set email alerts
|

Noonan syndrome‐like phenotype in a patient with heterozygous ERF truncating variant

Abstract: Craniosynostosis is caused by abnormalities of multiple signaling pathways, including excessive RAS signaling. Recently, a truncating variant in ETS2 repressor factor (ERF), a negative transcriptional regulator of the RAS pathway, was shown to be associated with craniosynostosis. Here, we report a 10-year-old male patient with a heterozygous nonsense mutation, p.Arg183*, in ERF who exhibited craniosynostosis with Noonan syndrome-like phenotypes. In consideration that loss-of-function variants in ERF would resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…A large proportion of the patients with pathogenic ERF variants who display syndromic craniosynostosis have features that overlap with those of Noonan syndrome. Yamada et al (2021) reported a patient with a Noonan syndrome-like phenotype associated with an ERF truncating variant. Other previous reports of ERF-related disorders did not describe a Noonan syndrome-like phenotype, but in some patients, overlapping phenotypes were noted retrospectively (Chaudhry et al, 2015;Glass et al, 2019;Körberg et al, 2020;Moddemann et al, 2022;Twigg et al, 2013;Yamada et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large proportion of the patients with pathogenic ERF variants who display syndromic craniosynostosis have features that overlap with those of Noonan syndrome. Yamada et al (2021) reported a patient with a Noonan syndrome-like phenotype associated with an ERF truncating variant. Other previous reports of ERF-related disorders did not describe a Noonan syndrome-like phenotype, but in some patients, overlapping phenotypes were noted retrospectively (Chaudhry et al, 2015;Glass et al, 2019;Körberg et al, 2020;Moddemann et al, 2022;Twigg et al, 2013;Yamada et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Yamada et al (2021) reported a patient with a Noonan syndrome-like phenotype associated with an ERF truncating variant. Other previous reports of ERF-related disorders did not describe a Noonan syndrome-like phenotype, but in some patients, overlapping phenotypes were noted retrospectively (Chaudhry et al, 2015;Glass et al, 2019;Körberg et al, 2020;Moddemann et al, 2022;Twigg et al, 2013;Yamada et al, 2021). A summary of the reported characteristics of patients with ERF variants is presented in Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,9 A recent case report described a child with a diagnosis of Noonan syndrome who was found to harbour a heterozygous ERF truncating variant. 10 Since the ‘™Rasopathies’™ are known to be associated with variable presentations of physiological and psychosocial developmental disorders 11,7,8 and given the involvement of ERF in RAS signal transduction, we hypothesised that reduced expression of ERF could be associated with similar features.…”
mentioning
confidence: 99%